2023
DOI: 10.1021/acs.jpclett.3c02252
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of S = 5/2 Zigzag-1D (2-Bromoethylammonium)3MnBr5 Antiferromagnet

Debendra Prasad Panda,
Diptikanta Swain,
Rajamani Raghunathan
et al.

Abstract: It has been challenging to design multifunctional lead-free organic−inorganic hybrid halides that can exhibit fascinating magnetic and photoluminescence properties since the dimensionality of the compounds has a contrasting impact on them. In this context, our newly synthesized compound (2-bromoethylammonium) 3 MnBr 5 (BEAMBr) crystallizes in the monoclinic C2/c space group with corner-sharing zigzag 1D chains of MnBr 6 distorted octahedra. Intriguingly, it exhibits a long-range antiferromagnetic ordering at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It is important to note that, lattice distortion can significantly impact the emission properties of a material and is often correlated with the STE emission . Previously, many OIH halides were reported, which shows strong bond length distortion (Δ d ) and STE emission (Figure a). ,, In R / S -APMCl, since two different types of ligands are bonded to the metal center, the bond lengths can differ significantly from each other (Figure b), and hence, polyhedral distortion can be high in this case. Therefore, we have calculated various parameters such as bond length distortion (Δ d ), bond angle variance (σ 2 ), octahedral elongation (λ oct ), octahedral edge deviation (DI), volume discrepancy V (%), and torsional or dihedral distortion (Θ) to quantify the octahedral distortion in both the structures. ,,, The octahedral distortion parameters are described in Supporting Information, and the calculated values are presented in Table .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is important to note that, lattice distortion can significantly impact the emission properties of a material and is often correlated with the STE emission . Previously, many OIH halides were reported, which shows strong bond length distortion (Δ d ) and STE emission (Figure a). ,, In R / S -APMCl, since two different types of ligands are bonded to the metal center, the bond lengths can differ significantly from each other (Figure b), and hence, polyhedral distortion can be high in this case. Therefore, we have calculated various parameters such as bond length distortion (Δ d ), bond angle variance (σ 2 ), octahedral elongation (λ oct ), octahedral edge deviation (DI), volume discrepancy V (%), and torsional or dihedral distortion (Θ) to quantify the octahedral distortion in both the structures. ,,, The octahedral distortion parameters are described in Supporting Information, and the calculated values are presented in Table .…”
Section: Resultsmentioning
confidence: 89%
“…STEs are transient defect species that emerge as a consequence of elastic lattice distortion by photoexcitation in a soft deformable lattice. Upon photoexcitation, free excitons are generated, which undergo self-trapping quickly due to the elastic lattice distortion stabilized by electron–phonon coupling in a low-dimensional compound with a soft liquid-like crystalline lattice. , Owing to the exciton self-trapping, the compound exhibits large Stokes shift, broad emission spectra, and long luminescence lifetime and is conducive for designing single-component white light LEDs. , Previously, several studies have demonstrated STE emission in hybrid manganese halides featuring Mn­(II) ions in tetrahedral coordination, showcasing red-emitting STE bands. Additionally, other reports have shown electron–phonon coupling mediated emission line width broadening in compounds where Mn­(II) ions exhibit both octahedral and tetrahedral coordination. Furthermore, our previous research has demonstrated analogous temperature-dependent emission behavior, leading to STE emission. , However, it is important to note that not all low-dimensional manganese hybrid halides exhibit similar temperature-dependent behavior . High polyhedral distortion plays a pivotal role in the resulting electron–phonon coupling-mediated STE emission.…”
Section: Introductionmentioning
confidence: 99%